Greening and Just Cities: Elements for Fostering a South–North Dialogue Based on a Systematic Literature Review - de Souza, Daniele Tubino; Torres, Pedro Henrique Campello (Frontiers in Sustainable Cities, 2021)
The design and deployment of green amenities is a way to tackle cities’ socio-environmental problems in the quest for urban sustainability. In this study, we undertake a systematic review of research published in international peer-reviewed journals that analyzes environmental justice issues within the context of the deployment of urban green amenities. Since most studies focus on the Global North, where this scholarship first emerged, our goal is to link the literature focused on the North and the South. This study aims to outline similarities and differences regarding the nexus of justice and the greening of cities in both contexts as well as to identify knowledge gaps in this scholarship in the Global South. “Green infrastructure” and “nature-based solutions,” as the leading concepts for cities’ greening agendas, are used as descriptors in combination with “justice” and/or “green gentrification” in searches undertaken of two bibliographic databases. Our results show there is a need to better delineate a research agenda that addresses such issues in a heterogeneous Global South context while gaining insights from advances made by research on the Global North.